Buying Behavior Patterns Between Traders and Buyers Reviewing From Islamic Business Ethics (Case Study in Wiradesa Market, Pakalongan Regency) - Dela Setiani; Sarmini Sarmini; Sakinah Sakinah; Hendri Hermawan Adinugraha; Ade Gunawan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
In a market environment, marketing can change and be completely uncertain as well as provide opportunities and threats as well as the emergence of competition. With such high competition, business people use all means to gain profits, even business people often ignore ethics and morals in running a business. The purpose of this research is to find out the pattern of consumer behavior towards the seller, to find out the contracts made in buying and selling transactions and to find out the products being traded are in accordance with sharia principles. This study used qualitative research methods. The results of observations and interviews with traders at the wiradesa market, said that the buying and selling carried out was in accordance with Islamic law and had implemented it, for example, honest sellers in measuring scales, fairness of prices, guaranteed quality of the products being traded and even if there were products that were not good, it would be delivered to the buyer with different price conditions, if the buyer wants to buy then the price will be determined according to the quality of the product.